Understanding changes in plant productivity using EVI satellite data in Tswalu Kalahari Reserve - Tokura, Wataru (Percy FitzPatrick Institute of African Ornithology, 2016)
In the arid African savanna, the limited availability of water strongly affects plant productivity, but other key drivers of vegetation dynamics, such as herbivory and fire, are usually considered to have a relatively minor impact. The main purpose of this study was to characterise the spatial and temporal pattern in plant productivity in the 100 000 hectare Tswalu Kalahari Reserve (TKR) in the semi-arid Northern Cape and relate the observed changes to potential drivers using medium spatial resolution of MODIS Enhanced Vegetation Index (EVI) time series data (16 day, 250 m) from 2000 to 2015. The time series of EVI for the past 16 years in TKR presented a highly seasonal pattern which fluctuated between years. A composite of annual small integrated value of EVI images highlighted spatial and temporal heterogeneity of plant productivity in the area. The EVI value was mainly influenced by rainfall and effect of fire and herbivory was considered to be minor. These observations confirmed the extreme variability of plant productivity in the drylands in the summer rainfall region of South Africa. Additionally, most of the values concerning the phenometrics of EVI differ significantly among vegetation types. This suggests that the structure and function of the vegetation determine plant productivity as well as their being a possible effect of soil property and reflectance. The trend in plant productivity computed by residual trend analysis (RESTREND) detected a significant positive trend in plant productivity in the east and south west of TKR, which overlapped with shrub-dominated vegetation, providing evidence for possible ongoing bush encroachment in these areas. On the other hand, a negative trend was detected in some locations in the west. The data generated from MODIS EVI and the small integrated value of EVI using TIMESAT produced biologically interpretable results. However, the correlative relationship between the EVI derived from Landsat Operational Land Imager (OLI) and plant cover estimated in the field was poor or not significant and needs to be examined further.